BEING PRESENT IS BEING INCLUDED? ANALYSIS OF SITUATIONS IN WHICH SCHOOL INCLUSION DOES NOT HAPPEN - Martins, Barbara Amaral [UNESP]; Chacon, Miguel Claudio Moriel [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2022)
Public students in Special Education should preferably attend regular schools. Despite advances in terms of legislation and enrollment, school inclusion does not always truly happen inside school institutions. Therefore, we aimed to describe and analyze classroom situations in which school inclusion does not really happen. The participants were 16 teachers and 22 public students from Special Education enrolled in public schools in Corumba and Ladario, Mato Grosso do Sul. The data was collected through filming and analyzed using the Protocol for Observation of Inclusive Educational Situations. Four classroom situations were considered not inclusive and revealed a lack of individualized attention from teachers to public students of Special Education, lack of curricular flexibility, offering activities unrelated to the work developed by other students and lack of pedagogical responses consistent with the level of development of these students.
Keywords: Special education; School inclusion; Educational exclusion; Target audience for special education